Análise da carga de trabalho em operadores de uma empresa logística da região sul - Pereira, Kezia Sayoko Matsui (2018)
In Brazil, the road segment has contributed to the generation of formal jobs in relation to the total volume of workers in the transportation sector. The characteristics of the functions in this branch have often exposed workers to risky conditions and high work demands. Therefore, the objective of this study was to identify the workload and the factors of influence of operators in activities of distribution of perishable loads. The methodology consisted of the application of the instruments: Sociodemographic questionnaire to identify the profile of the sample, NASA TLX Questionnaire adapted for workload analysis, Questionnaire to identify complaints of pain and semi-structured interview for the survey of the factors that influence the work load. The population consisted of 30 drivers and 20 helpers who worked distributing goods in a region that does not impose risks to the worker in relation to cargo theft and / or congestion, when compared to Brazilian metropolises. Questionnaires were applied in 73.33% of drivers and 55% of helpers working in two fixed shifts, shift 1 (2:00 am to 11:00 am) and shift 2 (business hours). Descriptive and inferential (non-parametric p-spearman) statistical analyzes were performed to evaluate the relationship between sociodemographic variables, NASA TLX dimensions and the perception of motorist and night shift aides (T1). Of the total number of NASA TLX respondents adapted, 55% of drivers and 22.22% of helpers perceived a balanced workload (scores ranging from 5 to 10 on the scale), meaning they were required to work at a level who are able to exercise the activities, not being discouraged or burdened with the task. The workload was presented in both groups as moderate and balanced. The drivers indicated effort (physical and mental) as the major influencer of the workload increase for both shifts T1 (2.35) and T2 (2.27), with morning drivers (T1) being the most demanded. Complaints of pain during work were low (less than 5, on a scale of 0 to 15), and there was virtually no pain at work. Only reports in the right arm, legs and hands in the drivers of shift 2, but at moderate levels (between 5 and 10). As identified by drivers, work difficulties may occur due to the context of the external environment (storage locations, road infrastructure, traffic conditions, customer relationship), environmental conditions (heat, cold, rain on deliveries). And mainly the lack of structure in satisfying the physiological needs (toilets). In general, there was a high satisfaction with work, but the greatest challenges for the minimization of the workload in these functions, are improvements to be implemented at the operational level, but mainly for the public policies regarding road transport infrastructure, which impact minimizing performance and increasing occupational risks. Suggested improvements: (i) short-term better accommodation of truck loads and agreements with establishments on delivery routes; (ii) medium-term studies on tool ergonomics; (iii) long-term design of truck design.